Polyester film and its uses
The use of a polyethylene naphthalate polyester film with a high temperature hold angle and easy adhesive layer addresses the issue of image distortion and deformation in folding displays, ensuring reliable and portable folding displays.
Patent Information
- Application Number
- JP2024018015
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-22
- Filing Date
- 2024-02-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-04-15
AI Technical Summary
Conventional folding display films deform over time due to repeated folding, leading to image distortion and poor mass production efficiency, especially at high temperatures.
A polyester film with a thickness of 10 μm to 125 μm, made from polyethylene naphthalate, featuring a high temperature hold angle of 70° or more in the bending direction, and an easy adhesive layer for improved adhesion.
The film maintains its shape and prevents image distortion after repeated folding, even at high temperatures, while ensuring mass production feasibility and excellent portability in portable terminal devices.
Smart Images

Figure 0007662070000003 
Figure 0007662070000004 
Figure 0007662070000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester film for a foldable display, a hard coat film for a foldable display, a foldable display, and a mobile terminal device, and more particularly to a foldable display and a mobile terminal device that are less susceptible to image distortion due to deformation of the film even when repeatedly folded, and the polyester film for the foldable display. [Background technology]
[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or similar.
[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used for not only video content and music, but also business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.
[0004] To achieve these goals, a method has been proposed to make the display more compact by connecting multiple displays together (see Patent Document 1). However, the invention in Patent Document 1 leaves a bezel, which means the image is cut off, resulting in reduced visibility and making this a problem that has not been widely adopted.
[0005] Meanwhile, in recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption of the image and are convenient to carry around.
[0006] In conventional displays and mobile terminal devices that do not have a folding structure, the surface of the display can be protected with a non-flexible material such as glass. However, in a folding display, when a single surface is displayed via a folding part, it is necessary to use a hard coat film or the like that is flexible and can protect the surface. However, in a foldable display, the area corresponding to a certain folding portion is repeatedly folded, and therefore the film in that area deforms over time, causing problems such as distorting the image displayed on the display. In addition to the surface protection film, films are used in various parts of a foldable display, such as polarizing plates, retardation plates, touch panel substrates, substrates for display cells such as organic electroluminescence (EL), and protective members for the back surface, and these films are also required to be durable against repeated folding.
[0007] In view of this, a method of partially changing the film thickness has been proposed (see Patent Document 2). However, the invention of Patent Document 2 has a problem in that the manufacturing process becomes complicated in order to change the film thickness, and mass productivity is poor.
[0008] A method for adjusting the refractive index in the bending direction of a polyester film has also been proposed (see Patent Document 3). However, there was a concern that a film using polyethylene terephthalate could not be used in applications requiring higher reliability (high temperature range). [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2010-228391 A [Patent Document 2] JP 2016-155124 A [Patent Document 3] International Publication No. 2018 / 150940 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention aims to solve the problems associated with conventional display components as described above, and provides a foldable display that is easy to mass-produce and has no risk of image distortion at the folded part after repeated folding, and a polyester film for foldable displays that makes it possible to provide a mobile terminal device equipped with such a foldable display. Furthermore, the present invention aims to provide a polyester film for folding displays that does not produce creases in the folded portions even in a high temperature range. [Means for solving the problem]
[0011] That is, the present invention comprises the following: 1. A polyester film for folding displays having a thickness of 10 μm or more and 125 μm or less and a high temperature hold angle in the bending direction of 70° or more. (Here, the high-temperature hold angle refers to the angle formed by the fold after heating at 85°C for 18 hours so that a strain of 1.7% is applied to both surfaces of the bent part. The bending direction refers to the direction perpendicular to the folded part.) 2. Density is 1.349g / cm 3 The polyester film for folding displays according to claim 1 above. 3. The polyester film for folding displays according to 1 or 2, wherein the polyester is polyethylene naphthalate. 4. The polyester film for folding displays according to any one of 1 to 3 above, having an easy-adhesion layer on at least one surface of the polyester film. 5. A foldable display in which the polyester film for a foldable display described in any one of 1 to 4 above is arranged as a back protective film, in which a continuous single polyester film is arranged through the folding portion of the foldable display. 6. A mobile terminal device having the foldable display described in claim 5. Effect of the Invention
[0012] A folding display using the polyester film for folding displays of the present invention maintains mass productivity, and the polyester film does not deform after repeated folding even in a high temperature range, and does not cause image distortion at the folded portion of the display. A mobile terminal device equipped with a folding display using such a polyester film provides beautiful images, is highly functional, and is convenient in terms of portability, etc. [Brief description of the drawings]
[0013] [Figure 1] FIG. 2 is a schematic diagram showing the bending radius when the foldable display of the present invention is folded. [Diagram 2] FIG. 2 is a schematic diagram showing the bending direction of the polyester film for folding displays according to the present invention. [Diagram 3] FIG. 13 is a schematic diagram for explaining a method for measuring a hold angle in a bending direction. [Figure 4] An enlarged schematic diagram of a sample film (reference numeral 4) sandwiched between two PTFE plates is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc. For example, LCD, organic EL, and inorganic EL having a bendable structure are preferable. In particular, organic EL and inorganic EL that can reduce the layer structure are particularly preferable, and organic EL with a wide color gamut is more preferable.
[0015] (Foldable display) A foldable display is a single continuous display that can be folded in half or the like when carried. By folding, the size can be halved, improving portability. The bending radius of a foldable display is preferably 5 mm or less, and more preferably 3 mm or less. If the bending radius is 5 mm or less, it is possible to make the display thinner when folded. It can be said that the smaller the bending radius, the better. With the present invention, even with such a bending radius, fold marks can be suppressed. The bending radius is preferably 0.1 mm or more, may be 0.5 mm or more, or may be 1 mm or more. Even if the bending radius is 0.1 mm, a practically sufficient thinness can be achieved when carried around. The bending radius when folded is a value measured at a location indicated by reference numeral 11 in foldable display 1 in the schematic diagram of Fig. 1, and means the radius of the inside of the folded part when folded. Note that the surface protection film described later may be located on the outside or inside of the folded foldable display. Furthermore, the foldable display may be folded in three or four, or may be a rollable type, all of which are considered to fall within the scope of the foldable display of the present invention. Furthermore, the polyester film of the present invention can be folded not only in the longitudinal direction as shown in FIG. 1, but also in the width direction.
[0016] The polyester film for folding displays of the present invention may be used in any part of a folding display as long as it is a component of the folding display. Below, a typical configuration of a folding display and the part in which the polyester film of the present invention can be used are described using an organic EL display as an example. Hereinafter, the polyester film for folding displays of the present invention may be simply referred to as the polyester film of the present invention.
[0017] (Foldable OLED display) The essential component of a folding organic EL display is an organic EL module, and further includes a circular polarizing plate, a touch panel module, a front protective film, a back protective film, and the like, as required. (Organic EL module) A typical structure of an organic EL module is an electrode / electron transport layer / light-emitting layer / hole transport layer / transparent electrode. The polyester film of the present invention can be used as a substrate on which an electrode is provided and an electron transport layer, a light-emitting layer, and a hole transport layer are further provided. In particular, it can be preferably used as a substrate for a transparent electrode. In this case, since the substrate film is required to have high barrier properties against water vapor and oxygen, it is preferable that the polyester film of the present invention is provided with a barrier layer such as a metal oxide layer. In order to improve the barrier properties, a plurality of barrier layers may be provided, or a plurality of polyester films provided with a barrier layer may be used.
[0018] (Touch panel module) It is preferable that the mobile terminal device has a touch panel. When an organic EL display is used, it is preferable that a touch panel module is disposed on the top of the organic EL display or between the organic EL module and the circular polarizer. The touch panel module has a transparent substrate such as a film and a transparent electrode disposed thereon. The polyester film of the present invention can be used as this transparent substrate. When used as a transparent substrate for a touch panel, it is preferable that the polyester film is provided with a hard coat layer or a refractive index adjustment layer.
[0019] (Circular polarizing plate) The circular polarizing plate suppresses deterioration of image quality due to reflection of external light by members inside the display. The circular polarizing plate has a linear polarizing plate and a retardation plate. The linear polarizing plate has a protective film on at least the viewing side surface of the polarizer. The polarizer may also have a protective film on the surface opposite to the viewing side, or the retardation plate may be directly laminated on the polarizer. The retardation plate is a resin film having a retardation such as polycarbonate or cyclic olefin, or a resin film provided with a retardation layer made of a liquid crystal compound. The polyester film of the present invention can be used as a polarizer protective film or a resin film for a retardation plate. In these cases, it is preferable that the slow axis direction of the polyester film of the present invention is parallel or perpendicular to the absorption axis direction of the polarizer. Incidentally, a deviation of 10 degrees, preferably 5 degrees, from this parallel or perpendicular direction is allowed.
[0020] (Surface protection film) When an impact is applied to a display from above, the circuit of an organic EL module or a touch panel module may be broken, so a surface protective film is often provided. The polyester film of the present invention is used as this surface protective film. Surface protective films include those called cover windows that are incorporated into the outermost surface of a display, and those called afters that can be attached, peeled off, and replaced by the user himself, but the polyester film of the present invention is used in either case. When the polyester film of the present invention is used as a surface protective film, it is preferable that a hard coat layer is laminated on at least the surface side of the polyester film. The hard coat layer is provided on the surface of a folding display with the hard coat layer on the viewing side. The hard coat layer may be provided on both sides.
[0021] (Back protection film) It is also preferable that a protective film is provided on the back side of the display. Specifically, an adhesive layer is provided on the non-visible side of the organic EL module and laminated. The polyester film of the present invention can be used as the protective film on the back side.
[0022] The polyester film of the present invention can also be used for applications other than those described above, so long as it is used in a portion that is folded as a component of a folding display. Among these, the polyester film of the present invention is preferably used as a cover window surface protection film, an after-surface protection film, a base film of a touch panel module, or a back surface protection film, and more preferably used as a cover window surface protection film or an after-surface protection film.
[0023] In addition, it is not necessary for the polyester film of the present invention to be used in all of the above-mentioned foldable displays. In addition to the polyester film of the present invention, polyimide films, polyamide films, polyamideimide films, polyester films other than the polyester film of the present invention, polycarbonate films, acrylic films, triacetyl cellulose films, cycloolefin polymer films, polyphenylene sulfide films, polymethylpentene films, and the like can be used in foldable displays according to their suitability.
[0024] The polyester film of the present invention may be a single-layer film made of one or more types of polyester resin, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.
[0025] Examples of polyester resins used in the polyester film include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, such as polyethylene-2,6-naphthalate, or copolymers mainly made of these resin components. Among these, polyethylene naphthalate films, particularly stretched polyethylene naphthalate films, are preferred in terms of mechanical properties, heat resistance, transparency, etc. In an embodiment in which polyethylene naphthalate resin is the main component and other polyesters are mixed in, the amount of the other polyester resins may be 40% by weight or less, for example 10% by weight or less, or 5% by weight or less, relative to 100% by weight of the resin in the polyester film, and less than 5% by weight is preferable. On the other hand, the polyethylene naphthalate resin may be present in an amount of 60% by weight or more, 90% by weight or more, or 95% by weight or more, relative to 100% by weight of the resin in the polyester film, and it is preferably present in an amount of, for example, more than 95% by weight. When the content of the other polyester resin is less than 5% by weight, the crystallinity of the polyester film can be kept high, and the high temperature hold angle can be kept good. In one embodiment, the proportion of polyethylene naphthalate in the raw material ratio of the polyester film is 100% by weight. In the present invention, the polyester film may contain a plurality of types of polyethylene naphthalates having different properties. By increasing the proportion of polyethylene naphthalate, the polyester film does not deform even after repeated folding in a high temperature range, and image distortion at the folding portion of the display can be suppressed. Furthermore, a mobile terminal device equipped with a folding display using the polyester film of the present invention provides beautiful images, is highly functional, and has excellent convenience such as portability.
[0026] When a polyester copolymer is used for the polyester film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 3% by mass. When it is less than 3% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.
[0027] In addition, in the production of polyester film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.40 to 1.0 dl / g. When the intrinsic viscosity is 0.40 dl / g or more, the impact resistance of the obtained film is improved, and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filtration pressure of the molten fluid does not increase too much, which is preferable, and film production can be easily and stably operated. For example, the intrinsic viscosity of at least one or more types of resin pellets is 0.40 to 0.8 dl / g, and the intrinsic viscosity may be 0.40 to 0.7 dl / g.
[0028] The thickness of the polyester film is 10 μm or more and 125 μm or less, and more preferably, for example, 25 μm or more and 100 μm or less. When the thickness is 10 μm or more, the effect of improving pencil hardness and impact resistance is observed, and when the thickness is 125 μm or less, it is advantageous for weight reduction and is excellent in flexibility, processability, handleability, and the like.
[0029] The surface of the polyester film of the present invention may be smooth or may have irregularities. When the film is used as a surface cover for a display, the film preferably has a smooth surface. The haze is preferably 3% or less, more preferably 2% or less, and particularly preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably as small as possible, but from the viewpoint of stable production, the haze is preferably 0.1% or more, and may be 0.3% or more.
[0030] As described above, in order to reduce haze, it is preferable that the film surface does not have too much unevenness. However, from the viewpoint of ease of handling, the film may have some unevenness in order to provide a certain degree of slipperiness. The surface irregularities can be formed by blending particles in the polyester resin layer on the surface, or by coating a coat layer containing particles during the film formation.
[0031] The method of blending the particles in the polyester resin layer can be a known method. For example, it can be added at any stage of polyester production, but preferably it can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of the transesterification reaction, and before the start of the polycondensation reaction, to proceed with the polycondensation reaction. It can also be performed by using a vented kneading extruder to blend the slurry of particles dispersed in ethylene glycol or water with the polyester raw material, or by using a kneading extruder to blend the dried particles with the polyester raw material.
[0032] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.
[0033] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).
[0034] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within a range that maintains the total light transmittance in a preferred range.
[0035] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. With a transmittance of 85% or more, sufficient visibility can be ensured. The higher the total light transmittance of the polyester film, the better, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less.
[0036] The maximum heat shrinkage rate of the polyester film after heat treatment at 150° C. for 30 minutes is preferably 2% or less, more preferably 1.5% or less, for example, 1.2% or less. A thermal shrinkage rate of 2% or less can suppress dimensional changes caused by heat generation in the organic EL display itself. The lower the thermal shrinkage rate, the better, but it is preferably -1% or more, and more preferably 0% or more. A negative value here means that the display expanded after heating, and a value below -1% may also result in poor flatness.
[0037] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming a hard coat layer or the like.
[0038] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.
[0039] In addition, the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, and can be formed by a general coating method, preferably a so-called in-line coating method.
[0040] The above-mentioned polyester film can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the monomer liquid is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and then stretched to form a base film.
[0041] Next, a method for producing a biaxially stretched polyester film will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the base film, but the present invention is not limited to this example. In addition, the number of layers, such as a single layer structure or a multilayer structure, is not limited. In addition, even in an embodiment in which a polyethylene naphthalate (PEN) film is used instead of the PET film, the polyester film according to the present invention can be produced in a similar manner.
[0042] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.
[0043] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 300° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.
[0044] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.
[0045] (Refractive index in bending direction) In the present invention, the refractive index of the polyester film in at least one of the longitudinal direction (machine flow direction) and the width direction is preferably 1.610 to 1.750, for example, 1.610 to 1.710, and more preferably 1.630 to 1.680. In one embodiment, the refractive index in the longitudinal direction of the polyester film is 1.610 or more, so that the crystallinity can be efficiently improved and the high-temperature hold angle can be improved. If the refractive index is 1.750 or less, the stress during bending can be reduced and both the hold angle at room temperature and the hold angle at high temperature can be improved. Conversely, when the refractive index in the width direction of the polyester film is within the above range, the refractive index in the longitudinal direction of the polyester film is desirably higher than the refractive index in the width direction of the polyester film. The refractive index of the polyester film in the bending direction is preferably 1.610 or more and 1.750 or less, for example, 1.610 or more and 1.710 or less, and more preferably 1.630 or more and 1.680 or less. Here, the bending direction refers to a direction perpendicular to a folding portion (reference number 21) assumed for use in a folding display, as shown by reference number 22 on the polyester film (reference number 2) in FIG. A refractive index of 1.610 or more and 1.750 or less in at least one of the longitudinal direction and the width direction is preferable because there is little deformation when repeatedly folded and there is no risk of degrading the image quality of the foldable display. The refractive index in the bending direction of the polyester film is more preferably 1.630 to 1.680. Of course, the direction is preferably the bending direction. If it is 1.610 or more, the crystallinity can be efficiently improved and the high temperature hold angle can be improved. If it is 1.750 or less, the stress during bending can be reduced and both the hold angle at room temperature and the high temperature hold angle can be improved. The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and the stretching temperature. A relaxation step in the stretching direction and multi-stage stretching may also be used to adjust the refractive index. When multi-stage stretching is performed, it is preferable to set the stretching ratios in the second and subsequent stages higher than the stretching ratio in the first stage.
[0046] By controlling the refractive index in at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index in the bending direction within the above range, fatigue due to the compressive stress applied to the inside of the fold when folded can be reduced. It is believed that fatigue due to compressive stress occurs mainly in the crystalline portion, and the less crystals there are in the bending direction, the less fatigue there is. Therefore, it is believed that the refractive index in the bending direction is smaller than the refractive index perpendicular to the bending direction, thereby reducing the amount of oriented crystals in the bending direction and suppressing compression fatigue.
[0047] Furthermore, the creep phenomenon caused by tensile stress applied to the outside of the fold when the material is folded can be suppressed by reducing the refractive index. Fatigue caused by tensile stress is thought to occur mainly in the amorphous portion, and the repeated application of stress causes molecular chains to align, resulting in deformation. It can be assumed that the fewer molecular chains aligned in the bending direction, the less deformation caused by alignment. Furthermore, since fatigue caused by tension can be suppressed with fewer amorphous portions, a higher degree of crystallinity, i.e., a higher density, is preferable.
[0048] In the present invention, the stretching ratio of the unstretched polyester sheet in at least one of the longitudinal direction (machine flow direction) and the width direction is preferably 1.0 to 3.4 times, more preferably 1.4 to 2.3 times. The stretching direction is preferably the bending direction. A stretching ratio of 3.4 times or less is preferable because it does not cause uneven thickness of the film. The stretching temperature is preferably 120°C to 150°C, more preferably 125°C to 145°C. The heating method during stretching can be a conventionally known method such as a hot air heating method, a roll heating method, or an infrared heating method. By setting the stretching temperature to 125°C to 145°C, it is possible to prevent significant unevenness in thickness due to stretching at the above stretching ratio.
[0049] (Refractive index in the direction of the fold) The refractive index of the polyester film in the direction perpendicular to the direction in which the refractive index is 1.610 or more and 1.750 or less is preferably 1.750 to 1.870. That is, the refractive index in the direction perpendicular to the bending direction (direction of the folded portion) is preferably 1.750 or more and 1.870 or less. By making it 1.750 or more and 1.870 or less, deformation when folded in the bending direction can be reduced. By making it 1.870 or less, cracks can be suppressed in the direction of the folded portion, and further, breakage can be suppressed. In addition, breakage during the winding process after stretching can be suppressed. By making it 1.750 or more, the density can be increased and the high temperature hold angle can be improved. For example, when the longitudinal direction of a polyester film is the bending direction, the direction perpendicular to the bending direction (direction of the folded portion) corresponds to the direction perpendicular to the bending direction (direction of the folded portion) in which the width direction of the polyester film is perpendicular to the bending direction. The refractive index in the direction perpendicular to the bending direction is more preferably 1.770 to 1.830. In addition, when comparing the refractive index in the bending direction with the refractive index in a direction perpendicular to the bending direction (the direction of the folded portion), it is desirable for the refractive index in the bending direction to be lower. This embodiment can reduce deformation when folded in the bending direction. It can also suppress cracks from occurring in the direction of the folded portion, and further suppress breakage. In addition, it can suppress breakage during the winding process after stretching. In addition, it can increase density and improve the high temperature hold angle. Methods for adjusting the refractive index in the direction perpendicular to the bending direction include the stretching ratio, stretching preheating temperature, stretching temperature, multi-stage stretching, and film relaxation. The stretching ratio is preferably 3.3 to 5.0 times, more preferably 3.5 to 4.5 times. The stretching preheating temperature in the direction perpendicular to the bending direction is preferably 125 to 145°C. When multi-stage stretching is performed in the direction perpendicular to the bending direction, it is preferable to set the stretching ratio higher in the second stage and thereafter than in the first stage. The film may be relaxed by 0 to 10% in either the machine flow direction (longitudinal direction) or the perpendicular direction (width direction).
[0050] (Refractive index in the thickness direction) The refractive index in the thickness direction is preferably 1.520 or less. More preferably, it is 1.515 or less, even more preferably, it is 1.510 or less, particularly preferably, it is 1.505 or less, and most preferably, it is 1.500 or less. Although it is preferable that the refractive index in the thickness direction is low, it is preferably 1.3 or more from the viewpoint of stable production, and may be 1.4 or more. It is particularly preferably 1.410 or more.
[0051] (Regarding density of polyester film) The density of polyester film is 1.349g / cm 3 It is preferable that the density is 1.350 g / cm or more. 3 More preferably, it is 1.350 g / cm or more. 3 By setting the density to 1.40 g / cm or more, the high temperature hold angle can be improved. The higher the density, the better. Although it depends somewhat on the presence or absence of particles in the film, a density of 1.40 g / cm or more is preferable. 3 It is preferable that the density is 1.395 g / cm or less, and more preferably 1.395 g / cm 3 The following is more preferred: The density of polyester film is 1.349g / cm 3 By satisfying the above conditions, the polyester film of the present invention can be sufficiently crystallized, and deformation at 85° C. can be suppressed. In addition, an increase in the thermal shrinkage rate can be suppressed, and dimensional changes due to heat generation of the device can be suppressed. By setting the heat setting temperature during film formation to 210 to 270° C., crystallization can be promoted and the density can be effectively increased within the above range.
[0052] The bending direction of the polyester film is preferably set to correspond to the longitudinal direction (machine flow direction). This makes it easier to reduce the refractive index in the bending direction by biaxial stretching and improve the flexibility. That is, a polyester film is preferably obtained by stretching an unstretched polyester sheet in the longitudinal direction at a stretching ratio of 1.0 to 2.3 times, more preferably 1.4 to 2.1 times. In addition, it can be said that a preferred embodiment is to stretch the polyester sheet in the transverse direction at a stretching ratio of 3.3 to 5.0 times, more preferably 3.5 to 4.5 times.
[0053] The polyester film of the present invention has a high-temperature hold angle in the bending direction of 70° or more. Here, the high-temperature hold angle refers to the angle formed by the fold marks after heating at 85°C and fixing for 18 hours so that a strain of 1.7% is applied to both surfaces of the bent portion. The bending direction refers to the direction perpendicular to the folded portion. The high temperature hold angle in the bending direction is 71° or more, for example, 72° or more. The higher the better, and 180° is most preferable, but the high temperature hold angle in the bending direction may be 180° or less, and for example, 170° or less still provides sufficient function. By having the high temperature hold angle in the bending direction within the above range, deformation at 85°C can be suppressed. In addition, the thermal shrinkage rate can be suppressed from increasing, and dimensional changes due to heat generation in the device can be suppressed. Therefore, according to the present invention, deformation does not occur after repeated folding even in high temperature regions, and image distortion at the folding portion of the display can be suppressed. Furthermore, mobile terminal devices equipped with a folding display using a polyester film provide beautiful images, are highly functional, and are convenient in terms of portability, etc. The method for measuring the high temperature hold angle in the bending direction will be exemplified in the Examples.
[0054] (Easy adhesion layer) In the present invention, in order to improve the adhesion between the polyester film and a hard coat layer, etc., it is also preferable to laminate an easy-adhesion layer on at least one side of the polyester film of the present invention. The easy-adhesion layer can be obtained by applying a coating liquid for forming the easy-adhesion layer to one or both sides of an unstretched or uniaxially stretched film in the longitudinal direction, heat-treating and drying as necessary, and then stretching the film in at least one direction that is not stretched. Heat treatment can also be performed after biaxial stretching. The final coating amount of the easy-adhesion layer is 0.005 to 0.20 g / m 2 It is preferable to control the coating amount to 0.005 g / m 2 On the other hand, if the coating amount is 0.20 g / m or more, adhesiveness is obtained, which is preferable. 2 If it is not more than this, blocking resistance can be obtained, which is preferable.
[0055] Resins contained in the coating liquid used for laminating the easy-adhesion layer can be, for example, polyester resins, polyether polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins, acrylic resins, etc., and can be used without particular limitation. Examples of crosslinking agents contained in the coating liquid for forming the easy-adhesion layer include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. Two or more of each can also be mixed and used. Due to the nature of in-line coating, these are preferably applied using a water-based coating liquid, and the resins and crosslinking agents are preferably water-soluble or water-dispersible resins or compounds.
[0056] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the easy-adhesion layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.
[0057] The coating liquid can be applied by a known method, similar to the coating layer described above, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.
[0058] (Hard coat layer) When the polyester film of the present invention is used as a surface protection film for protecting a folding display by placing it on the surface of the display, it is preferable that the polyester film has a hard coat layer on at least one surface. The hard coat layer is preferably placed on the display surface side of the polyester film and used in the display. The resin for forming the hard coat layer can be any of acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, epoxy, and other resins without any particular limitation. Two or more materials can be mixed and used, or particles such as inorganic filler or organic filler can be added.
[0059] (Thickness of hard coat layer) The thickness of the hard coat layer is preferably 1 to 50 μm. If the thickness is 1 μm or more, it is preferable because it is cured sufficiently and has a high pencil hardness. Furthermore, if the thickness is 50 μm or less, curling due to cure shrinkage of the hard coat can be suppressed, and the handling properties of the film can be improved.
[0060] (Application method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.
[0061] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, and is preferably cured by ultraviolet rays or electron beams in order to reduce damage to the film.
[0062] (Pencil hardness) The pencil hardness of the hard coat layer is preferably 3H or more, more preferably 4H or more. If the hard coat layer has a pencil hardness of 3H or more, it is not easily scratched and does not reduce visibility. In general, the pencil hardness of the hard coat layer is preferably high, but it may be 9H or less, 8H or less, or even 6H or less can be used without any practical problems.
[0063] (Characteristics of hard coat layer) The hard coat layer in the present invention can be used for the purpose of protecting a display by increasing the pencil hardness of the surface as described above, and preferably has a high transmittance. The total light transmittance of the hard coat film is preferably 87% or more, more preferably 88% or more. If the transmittance is 87% or more, sufficient visibility can be obtained. The total light transmittance of the hard coat film is generally the higher the better, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less. In addition, the haze of the hard coat film is generally preferably low, and preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower the haze, the better, but from the viewpoint of stable production, it is preferably 0.1% or more, and may be 0.3% or more.
[0064] The hard coat layer may further have other functions added thereto. For example, a hard coat layer having the above-mentioned functions such as an antiglare layer having a certain pencil hardness, an antiglare antireflection layer, an antireflection layer, a low reflection layer, and an antistatic layer is preferably used in the present invention.
[0065] A hard coat layer may also be provided when used as a substrate film of a touch panel module. When an ITO layer is used as a transparent electrode layer of a touch panel module, for example, a refractive index adjustment layer is preferably provided between the substrate film and the transparent electrode layer to make the electrode pattern less visible. In this case, the hard coat layer itself may also serve as a refractive index adjustment layer, or a separate layer for refractive index adjustment may be laminated.
[0066] In another embodiment, the polyester film for a folding display of the present invention can be used in a folding display arranged as a back protective film. For example, the polyester film for a folding display of the present invention can be arranged in a single polyester film that is continuous through the folding portion of the folding display.
[0067] In another aspect, a mobile terminal device is provided having a polyester foldable display of the present invention. EXAMPLES
[0068] Next, the present invention will be described with reference to examples and comparative examples. First, the evaluation methods of the characteristic values carried out in the present invention will be described below.
[0069] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, an Ubbelohde viscometer was used to measure the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone, and the intrinsic viscosity was calculated from the ratio of these times using the Huggins equation, assuming that the Huggins constant is 0.38. The same calculation formula was used to evaluate both polyethylene terephthalate (PET) and polyethylene naphthalate (PEN).
[0070] (2) Refractive index Using a Metricon laser refractometer (Model 2010 prism coupler), one sample film was clamped at a pressure of 40 on the built-in pressure gauge, and measurements were performed with a laser beam of 633 nm wavelength to obtain a spectrum chart. On the spectrum chart obtained, the point where the detector output suddenly dropped was read, and this value was taken as the refractive index. The refractive index in the longitudinal and width directions was measured in measurement mode TE, and the refractive index in the thickness direction was measured in measurement mode TM.
[0071] (3) Total light transmittance, haze The haze was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.).
[0072] (4) Density The density was measured according to the method compliant with JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).
[0073] (5) Maximum heat shrinkage rate The sample film was cut to 10 mm length x 250 mm width, and marks were made at 200 mm intervals along the long side in the direction to be measured, and the distance A between the marks was measured under a constant tension of 5 g. The sample film was then left in an oven at 150°C for 30 minutes without load, and then removed from the oven and cooled to room temperature. The distance B between the marks was then measured under a constant tension of 5 g, and the thermal shrinkage rate (%) was calculated using the following formula. The thermal shrinkage rate was measured at three equal positions in the width direction of the sample film, and the average value of the three points was taken as the thermal shrinkage rate (%). Heat shrinkage rate (%) = [(AB) x 100] / A The sample film is cut so that the length and width of the sample differ in both the bending direction and the folding direction, and measurements are taken. The data in the direction where the measured value is greater is regarded as the maximum heat shrinkage rate (%).
[0074] (6) High temperature hold angle The strength of the break mark that is created when the bent part is fixed so that a strain of 1.7% is applied to both surfaces is evaluated. FIG. 3 is a schematic diagram for explaining the method of measuring the hold angle in the bending direction. A sample film (reference number 3) was cut to 10 mm in the width direction and 50 mm in the flow direction. Two PTFE plates (reference number 31) were overlapped, and in the case of a 50 μm sample film, a gap was created by sandwiching a 3 mm thick PTFE plate (reference number 32) between them as a spacer. Double-sided tape was attached to both ends of the sample, and in a bent state, the sample was sandwiched between the 3 mm gap between the PTFE plates, and both ends were fixed with double-sided tape. After leaving it in an 85°C dry environment for 18 hours, the angle (reference number 33) between the fold marks on the film was measured 5 minutes after it was removed from between the two PTFE plates (reference number 31). This angle was taken as the high-temperature hold angle. In order to keep the strain constant, the thickness 32 of the PTFE plate used as the spacer is changed depending on the thickness of the film. Figure 4 shows an enlarged schematic diagram of the sample film (reference number 3) sandwiched between two PTFE plates (reference number 31 in Figure 3). The neutral plane, where neither compressive stress nor tensile stress is applied, is defined as the center in the thickness direction (dashed line in the figure), and the difference between the neutral plane and both surfaces is defined as the strain. In other words, the strain applied to both surfaces can be expressed by the following formula. In FIG. 4, reference numeral 41 denotes the diameter of the outermost surface of the sample film, reference numeral 42 denotes the diameter of the neutral surface of the sample film, and reference numeral 43 denotes the diameter of the innermost surface of the sample film.
[0075] In evaluating the high temperature hold angle, the strain (1.7%) can be expressed in the following way: Strain (1.7%) = (|Semicircumference of the outermost or innermost surface - Semicircumference of the midplane| / Semicircumference of the midplane) x 100 Here, the semicircumference can be calculated by the following formula, where t (mm) is the thickness of the sample film and d (mm) is the bending diameter (diameter of the outermost surface), i.e., the thickness of the spacer used. Semicircumference of the outermost surface = d × π / 2 Semicircumference of the midplane = (dt) × π / 2 Semicircumference of the innermost surface = (d-2t) × π / 2 From the above, when the strain is set to 1.7%, the thickness of the sample film is t (mm), the bending diameter, i.e., the thickness of the spacer used is d (mm), and the thickness of the spacer used (PTFE plate) is determined by the following formula. The spacer thickness for a typical film thickness is shown, for example, as follows. Spacer thickness d (mm) = film thickness (mm) x 60 For example, in the case of the sample film having a thickness of 50 μm, the diameter of the outermost surface (reference number 41) is 3 mm, which is the same as the thickness d of the spacer. The diameter of the innermost surface (reference number 43) is 2.9 mm, and the diameter of the neutral surface (reference number 42) is 2.95 mm. Here, in the equation showing the above strain, the semicircle of the outermost surface and the semicircle of the innermost surface can be appropriately selected.
[0076] (Preparation of polyethylene naphthalate pellets) 100 parts of dimethyl naphthalene-2,6-dicarboxylate and 60 parts of ethylene glycol were used with 0.03 parts of manganese acetate tetrahydrate as an ester exchange catalyst, and the temperature was gradually raised from 150°C to 238°C for 120 minutes to carry out an ester exchange reaction. When the reaction temperature reached 170°C, trimethyl phosphate (added as a solution heated in ethylene glycol at 135°C for 5 hours under a pressure of 0.11 to 0.16 MPa: 0.023 parts in terms of trimethyl phosphate) was added, and after the ester exchange reaction was completed, 0.024 parts of antimony trioxide was added. The reaction product was then transferred to a polymerization reactor, heated to 290°C, and polycondensation reaction was carried out under a high vacuum of 27 Pa or less to obtain polyethylene-2,6-naphthalenedicarboxylate having an intrinsic viscosity of 0.48 dl / g and containing substantially no particles.
[0077] (Preparation of polyethylene terephthalate pellets) A continuous esterification reaction apparatus consisting of a three-stage complete mixing tank equipped with an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reaction apparatus. TPA was set at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms would be 160 ppm relative to the PET produced. These slurries were continuously supplied to the first esterification reaction vessel of the esterification reaction apparatus and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to a second esterification reactor, EG distilled from the first esterification reactor was fed into the second esterification reactor in an amount of 8% by mass relative to the produced polymer (produced PET), and an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260° C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET was added, and reacted at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reaction vessel was continuously supplied to a three-stage continuous polycondensation reaction apparatus to carry out polycondensation, and was then filtered through a stainless steel sintered filter medium (nominal filtration accuracy: 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) having an intrinsic viscosity of 0.58 dl / g.
[0078] (Polymerization of urethane resin) A four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer was charged with 72.96 parts by mass of 1,3-bis(isocyanate methyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol having a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as a solvent, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C. While stirring and mixing at 2000 min-1, an isocyanate group-terminated prepolymer was added and dispersed in water. Thereafter, acetonitrile and a portion of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35 mass %.
[0079] (Polymerization of Water-soluble Carbodiimide Compounds) In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimide catalyst were added, and the mixture was stirred for 10 hours at 180°C under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100°C for 24 hours. Water was gradually added to the mixture at 50°C to obtain a yellow, transparent, water-soluble carbodiimide compound (B) with a solid content of 40% by mass.
[0080] (Preparation of Coating Solution for Forming Adhesion Layer) The following coating materials were mixed to prepare a coating solution. Water 16.97 parts by mass Isopropanol 21.96 parts by weight Polyurethane resin (A) 3.27 parts by weight Water-soluble carbodiimide compound (B) 1.22 parts by mass Particles 0.51 parts by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant 0.05 parts by weight (Silicone-based, solids concentration 100% by mass)
[0081] Example 1 Pellets of polyethylene naphthalate were fed into an extruder and melted at 310°C. This polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particles 95% cut), extruded into a sheet from a die, and then brought into contact with a casting drum with a surface temperature of 60°C using an electrostatic casting method, cooled and solidified, to produce an unstretched film. The above-mentioned coating liquid for forming an easy-adhesion layer was applied to both sides of the unstretched film by a roll coating method, and then dried at 80°C for 20 seconds. The coating amount after the final drying (after biaxial stretching) was 0.06 g / m 2The film was then introduced into a tenter, preheated at 140°C, transversely stretched 4.2 times at 135°C, fixed at the width, heat-set at 240°C for 5 seconds, and further relaxed by 1% in the width direction at 180°C to obtain a polyethylene naphthalate film with a thickness of 50 μm. The evaluation results are shown in Table 1.
[0082] (Examples 2 to 6) An unstretched film was obtained in the same manner as in Example 1, and then the unstretched film was uniformly heated to 120°C using a heating roll, heated to 135°C using a non-contact heater, and roll-stretched (longitudinal stretching) at the MD ratio shown in Table 1. A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to that shown in Table 1.
[0083] Example 7 An unstretched film was obtained in the same manner as in Example 1, and then the unstretched film was uniformly heated to 120°C using a heating roll, heated to 140°C using a non-contact heater, and roll-stretched (longitudinal stretching) at the MD magnification shown in Table 1. A polyester film was obtained in the same manner as in Example 1, except that the stretching magnification in the longitudinal direction was changed to that shown in Table 1.
[0084] Comparative Example 1 Pellets of polyethylene terephthalate were fed into an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded into a sheet form from a die, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. This unstretched film was uniformly heated to 75°C using a heating roll, heated to 85°C using a non-contact heater, and roll-stretched (longitudinal stretching) by 1.4 times. The above-mentioned adhesive layer forming coating solution was applied to both sides of the obtained uniaxially stretched film by roll coating, and then dried at 80° C. for 20 seconds. The final coating amount after drying (after biaxial stretching) was 0.06 g / m 2The film was then introduced into a tenter, preheated at 105°C, transversely stretched 4.0 times at 95°C, fixed in width, heat-set at 230°C for 5 seconds, and further relaxed in the width direction by 4% at 180°C to obtain a polyethylene terephthalate film with a thickness of 50 μm.
[0085] Comparative Example 2 As shown in Table 1, a polyester film was obtained in the same manner as in Comparative Example 1, except that the stretching ratio in the longitudinal direction was changed to 1.4 times.
[0086] The obtained polyester film was attached to the non-visible side of the organic EL module via a 25 μm thick adhesive layer, and a smartphone-type foldable display was created that can be folded in half at the center of the entire display with a radius of 3 mm, which corresponds to the bending radius in FIG. 1. The polyester film was placed on the non-visible side of a single continuous display via the folding portion, and was attached to a polyimide film having a barrier layer, which is an organic EL substrate. The polyester films of each example were used and satisfied the operation and visibility as a smartphone that can be folded in half at the center and carried around. In addition, there were no problems with operation and visibility even at high temperatures. On the other hand, in the case of the foldable displays using the polyester films of the comparative examples for the same purpose, as the frequency of use at high temperatures increases, image distortion appears at the foldable portion of the display, which is not very favorable. In addition, some of the displays had dents and scratches on the surface.
[0087] [Table 1A]
[0088] [Table 1B] [Industrial Applicability]
[0089] A folding display using the polyester film for folding displays of the present invention maintains mass productivity, and for example, the polyester film located on the back surface of the folding display does not deform after repeated folding, so that no image distortion occurs at the folded portion of the display. In particular, a mobile terminal device or image display device equipped with a folding display using the polyester film of the present invention as a back surface protective film provides beautiful images, is highly functional, has excellent convenience such as portability, and is highly reliable. [Explanation of symbols]
[0090] 1: Foldable display 11: Bending radius 2: Polyester film for surface protection of folding displays 21: Folding section 22: Bending direction (direction perpendicular to the folding part) 3: Sample film 31: PTFE board 32: Spacer 33: Hold angle 41: Outermost diameter 42: Midplane diameter 43: innermost diameter
Claims
1. The refractive index in the bending direction is 1.644 or more and 1.730 or less, the refractive index in the folding direction is 1.770 or more and 1.854 or less, the refractive index in the thickness direction is 1.486 or more and 1.508 or less, and the density is 1.349 g / cm 3 The polyethylene naphthalate film as described above, Polyethylene naphthalate film for folding displays having a high-temperature hold angle in the bending direction of 70° or more: Here, the high temperature hold angle refers to the angle formed by the fold marks after fixing the bent portion for 18 hours under heating at 85° C. so that a strain of 1.7% is applied to each of the surfaces of the bent portion. The bending direction refers to the direction perpendicular to the folded portion.
2. The polyethylene naphthalate film for folding displays according to claim 1, having a total light transmittance of 85% or more.
3. The polyethylene naphthalate film for folding displays according to claim 1, having an easy-adhesion layer on at least one surface of the polyethylene naphthalate film.
4. A foldable display comprising the polyethylene naphthalate film for a foldable display according to any one of claims 1 to 3 and a polarizer, the polyethylene naphthalate film being disposed on at least a viewing side surface of the polarizer, A foldable display, wherein the polyethylene naphthalate film is disposed as a continuous single polyethylene naphthalate film across a fold of the foldable display.
5. A mobile terminal device comprising the foldable display according to claim 4.
Citation Information
Patent Citations
Method of processing hard coat film, hard coat film and protective film
JP2010228391A
Light-emitting element, light-emitting device, electronic apparatus and luminaire
JP2014150249A
Manufacturing method for foldable hard coating film
JP2016155124A
Polyester film for surface protective film of flexible display
JP2020012087A
JPP7447994B